Evaluating the intention to purchase genetically modified food by consumers in Panama - Marín-Díaz, Agzel (2024)
Genetically modified (GM) foods are important because of their ability to increase crop yields, resist disease and adverse weather conditions, and improve nutritional quality. However, their use generates controversy because of concerns about food safety, benefits and risks due to their consumption. It is therefore necessary to evaluate the importance of these variables. The current study evaluated the variables that explain consumers' intention to purchase GM food in Panama. It was carried out by prospective, quantitative, non-experimental, and correlational research of 385 consumers. A multivariate technique evaluated the model proposed in the current study. Attitude toward food safety showed a negative effect on perceived risks from GM food and a positive effect on perceived benefits from GM food. Also, Perceived risks from GM food presented a negative and significant effect on Attitudes towards GM food and Perceived benefits from GM food showed a positive and significant effect on Attitudes towards GM food. Finally, Attitudes towards GM food positively affected GM food purchase intention. Firms can use these outcomes to prepare new strategies for communication about their products with GM components. Also, governments can use the information to create education programs for the population about GM foods, benefits and risks. Future studies in other regions are needed.